Spectrum of Influenza B Viral Infection in Indian Children: A Tertiary Centre Experience - Kini, Sandesh; Bhat Y, Ramesh; Handattu, Koushik; Kousika, Phalguna; Thunga, Chennakeshava (Journal of Nepal Paediatric Society, 2018)
Introduction: Influenza viral infection in children can range from subclinical illness to multi system involvement. The morbidity associated with influenza B viral infection is often overlooked. India being the second most populous country, accounts for 20% of global childhood deaths from respiratory infections. There is paucity of data on the clinical features and complications of influenza B viral infections in children from the Indian subcontinent. Our objective was to study the clinical profile, seasonality, complications and outcome associated with Influenza B viral infection in children < 18 years of age. Material and Methods: We conducted a retrospective observational study at a tertiary care hospital in South India. Children less than 18 years of age admitted to our paediatric unit were included in the study. We reviewed the case sheets of 56 patients who tested positive for influenza B virus during the study period and recorded their clinical and laboratory data. Throat swab obtained from cases were tested by RT-PCR. The illness was classified as upper respiratory tract infection, pneumonia and severe pneumonia. Outcome measures analysed were- mortality, need for oxygen supplementation or assisted ventilation, duration of oxygen support, duration of ICU/ hospital stay and time for defervescence following initiation of oseltamivir therapy. Results: The mean age of the study population was 6.98 years. Majority of the affected children were > 5 years of age in the school going category with a male to female ratio of 3:2. The diagnosis based on clinical and radiological findings included upper respiratory tract infection (URTI) in 44 (78.5%) cases followed by pneumonia in 11(19.6%) and severe pneumonia in one (1.7%) child. The peak incidence was in the month of March. Malnutrition was the most common risk factor affecting 22 (39.3%) cases followed by history of asthma in eight (14.3%). Three children required oxygen supplementation at admission. The median duration of hospital stay was seven days. The median duration for defervescence following initiation of oseltamivir therapy was 24 hours. Mortality was recorded in one infant who died of acute respiratory distress syndrome. Conclusions: Influenza B virus should be screened in all children having underlying high risk medical condition, presenting with pneumonia or upper respiratory tract infection. Oseltamivir therapy should be initiated early in the management of influenza B viral infections to prevent complications.